Effect of Risk Information Exposure on Consumers' Responses to Foods with Insect Contamination. Issue 2 (21st January 2014) - Kimura, Atsushi; Magariyama, Yukio; Miyanoshita, Akihiro; Imamura, Taro; Shichiri, Kumiko; Masuda, Tomohiro; Wada, Yuji
Abstract This study explores the impact that scientific information about insect contamination of food has on consumer perceptions. Participants (n = 320, Japanese consumers) were randomly assigned to 1 of 8 information‐type conditions: (1) information about insect type, (2) information about contamination processes, (3) information about the safety of contaminated food, (4, 5, 6) combinations of 2 of (1), (2), and (3) above, (7) all information, and (8) no‐information, and asked to rate their valuation, behavioral intention, and attitude toward food with insect contamination. Results demonstrated that some combinations of scientific information that include the safety of the contaminated food are effective to reduce consumers' compulsive rejection of insect contamination in food, whereas the single presentation of information about insect type increases consumers' explicit rejection of both the contaminated product and the manufacturer. These findings have implications for the coordination of risk communication strategies.